Study On Water-Soluble Polymers For Biomedical Applications - Oung, Hor Yen (Universiti Sains Malaysia, 2022)
Polymeric products have many remarkable properties which make them to be widely used in daily life. However, the downside of polymers is the accumulation of plastic waste globally. In this research, water-soluble polymers were investigated for a hollow plastic tube for the PI collector; which is used to collect urine in healthcare segment. The structural, chemical, mechanical, thermal properties and rate of solubility of the tubes are investigated. Apart from that, the PI collector tank is also subjected to microbes’ growth, urine odor and calcium precipitation which may potentially damage the PI collector. Thus, we intend to fabricate a soluble polymer film that is antiseptic in nature to suppress the microbes’ growth, contains a deodorant to reduce the smell and hasa decalcifier to chelate and trap the calcium salt. Several characterization techniques, including FTIR, tensile testing, DSC, swelling and dissolution studies for phase one whereas AAS, physical smelling and ATP test for phase two were performed. In phase one, the optimized extrusion temperatures at the feed zone/melting zone/die zone of the extruder for PVOH tubes were 185/201/203/182°C respectively with a screw speed of 7 rpm. The average tensile stress and elongation at break of the polymeric tube is 11.38 MPa and 1884.33% respectively. The PVOH tube recorded a melting point of 283.19°C. When immersing in tap water, the tubes swelled up at room temperature and 40°C before dissolving after 6 and 4 hours respectively. Whereas, the tubes dissolved completely after 3 and 2 hours of immersion at 50°C and 60°C. At 60°C, the PVOH tube showed the highest dissolution rate of 0.03903 mol/L h. In phase two, 4 ml of AA to decalcify the artificial urine whereas 5 ml of BKC is effective to reduce the contaminants count as well as deodorize the artificial urine.